Undergraduates’ experiences and attitudes of writing in L1 and English - Ansarimoghaddam, Shokoufeh; Bee, Hoon Tan (Penerbit UKM, 2014)
Writing is considered an important language skill. Although the importance of writing is undeniably realized and highly stressed by ESL scholars, educators and instructors, most ESL tertiary students and young graduates find creating a coherent and extended piece of writing difficult and challenging. Therefore, to overcome this problem, there is a need to be aware of the students’ experiences and attitudes to writing in their first language and English language. This research is a quasi-experimental study that employs a mixed-method approach. Participants were 30 tertiary ESL students enrolled in an obligatory course in the first year of Bachelor of Arts (English) programme. The study compares participants’ writing experiences and attitudes using questionnaire as the instrument for data collection. An interview was also conducted as a triangulation measure. Results suggest that participants mostly preferred using English language for various writing activities. Moreover, overall items of the questionnaire revealed that the there was no significant difference between the participants’ writing attitudes in their first language and English language. Furthermore, with regard to each item of the questionnaire, three of them showed significant difference. Although the remaining items did not show any significant difference, most of the items did receive higher mean for attitude to writing in English than first language. Participants’ interview responses revealed various reasons for their attitude, which supported findings obtained from the questionnaire analysis. The findings of the present study contribute to a better understanding of why some of the students do not like to write. Considering those reasons, instructors can then help their students to improve on their writing skill.